Hanging manoeuver for a left hepatectomy using Glisson's approach with a focus on tape position in liver hilum. Issue 9 (2nd December 2012) - Kim, Seoung Hoon; Kim, Young Kyu
Abstract Background Successful use of the hanging manoeuver during a hepatic resection requires the tape to be placed anatomically. The aim of this study is to describe the outcomes after variations in tape placement while using the hanging manoeuver during a left hepatectomy. Methods A whole cohort in whom the hanging manoeuver was attempted for a left hepatectomy from March 2003 to October 2011 was divided chronologically into three groups based on the tape position in the hilum along the ligamentum venosum (LV); conventionally between the right and left Glisson's pedicles (group 1), at the ventral side of the LV (group 2), and at the dorsal side of the LV (group 3). Patient characteristics, operative outcomes and complications defined using Clavien's classification were compared. Results A total of 151 patients were enrolled in one of three groups: group 1 (n = 54), group 2 (n = 35), and group 3 (n = 62). The hanging tape was successfully positioned in all patients as planned in the three groups. In group 2 and 3, the hanging manoeuver was continuously applied during a parenchymal transection. The Glisson's pedicle injury during hilar dissection was more common in group 2 (%, 51.4 versus 5.6 in group 1 and 3.2 in group 3; P = 0.001). Group 3 showed a shorter median operative time (min, 151 versus 210 in group 1 and 220 in group 2; P = 0.001), a shorter median hospital stay (days, 7 versus 10 in group 1 and 2; P = 0.012) and a lower complication rate (%, 1.6 versus 13.0 in group 1 and 37.1 in group 2; P = 0.001) without any operative mortality, major morbidity, blood transfusion or reoperation. Conclusions The hanging manoeuver had 100% feasibility with good outcomes during a left hepatectomy. The tape should be positioned to surround the left Glisson's pedicle and LV together as this helps to protect the caudate lobe.